Driver compliance to take-over requests with different auditory outputs in conditional automation. (December 2017) - Forster, Yannick; Naujoks, Frederik; Neukum, Alexandra; Huestegge, Lynn
Highlights: A visual-auditory Human-Machine Interface for take-over requests in conditional automation is proposed. The work focuses on the comparison of generic auditory output to additional semantic speech-based output. Shorter reaction times for the termination of the non-driving related task (i.e., reading a print magazine) and putting hands on the steering wheel were found when speech output was presented. Subjectively drivers were in favor of the speech-based system Abstract: Conditionally automated driving (CAD) systems are expected to improve traffic safety. Whenever the CAD system exceeds its limit of operation, designers of the system need to ensure a safe and timely enough transition from automated to manual mode. An existing visual Human-Machine Interface (HMI) was supplemented by different auditory outputs. The present work compares the effects of different auditory outputs in form of (1) a generic warning tone and (2) additional semantic speech output on driver behavior for the announcement of an upcoming take-over request (TOR). We expect the information carried by means of speech output to lead to faster reactions and better subjective evaluations by the drivers compared to generic auditory output. To test this assumption, N = 17 drivers completed two simulator drives, once with a generic warning tone ('Generic') and once with additional speech output ('Speech + generic'), while they were working on a non-driving related task (NDRT; i.e., reading a magazine). Each drive incorporated one transition from automated to manual mode when yellow secondary lanes emerged. Different reaction time measures, relevant for the take-over process, were assessed. Furthermore, drivers evaluated the complete HMI regarding usefulness, ease of use and perceived visual workload just after experiencing the take-over. They gave comparative ratings on usability and acceptance at the end of the experiment. Results revealed that reaction times, reflecting information processing time (i.e., hands on the steering wheel, termination of NDRT), were shorter for 'Speech + generic' compared to 'Generic' while reaction time, reflecting allocation of attention (i.e., first glance ahead), did not show this difference. Subjective ratings were in favor of the system with additional speech output.